ChemInform Abstract: A New Method for the Synthesis of Difluoromethyl Enol Ethers by O‐Difluoromethylation of 1, 3‐Diones with ClCF2CO2Et. Issue 28 (25th June 2015) - Lin, Xiaoxi; Weng, Zhiqiang
Abstract A convenient protocol for the direct conversion of five‐ and six‐membered cyclic 1, 3‐diones to difluoromethyl enol ethers is developed using difluoro carbene as reagent which is generated in situ from ethyl chlorodifluoroacetate.